Relationship between lower limb muscle strength and knee function with quality of life after anterior cruciate ligament reconstruction patients: a literature review - Ni Putu Aprilia Chintya Dewi; I Putu Gde Surya Adhitya; Anak Agung Gede Angga Puspa Negara (PT. Kesehatan Gerak Fungsi Tubuh, 2023)
Background: Anterior Cruciate Ligament Reconstruction (ACLR) is an orthopedic surgical procedure used to restore a functional knee. Surgical treatment in the form of ACL reconstruction can be performed to optimize quality of life after ACL injury. Decreased knee function after ACLR is closely related to a person's quality of life in the long term considering that the knee and other lower limbs have a crucial role in mobilizing and controlling the human body. Objective: To determine if there is a relationship between lower limb strength after ACL reconstruction and knee function also quality of life. Methods: The research method used is a literature review method using secondary data sources through a database of various scientific treatises accessible from internet sites. Scientific papers were searched using keywords such as ACL reconstruction, lower limb strength, knee function, and quality of life to facilitate proper literature retrieval. Result: Based on the results of the journal study, it was found that there was a decrease in lower extremity muscle strength and a decrease in knee function compared to participants who did not experience ACL injury-ACLR which caused a decrease in the quality of life of a person so that the preference of physical activity carried out in daily activities also changed with a low level of satisfaction from the expectations and expectations of individuals with ACLR. Conclusion: Based on some literature that has been discussed, there may be a correlation between the strength of the lower extremities and knee function with the quality of life of a person after anterior cruciate ligament reconstruction with the main predictor of decreased performance in daily physical activity which is closely related to the main function of the lower extremities, especially the knee.